2010
DOI: 10.1007/s00464-010-0997-y
|View full text |Cite
|
Sign up to set email alerts
|

Registering the critical view of safety: photo or video?

Abstract: Photo prints are inferior to video images for judging achievement of CVS. Therefore, a practical and logistical solution must be devised in hospitals for storage and insight in all video documentation, for example, by implementation of a link with the electronic patient database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 11 publications
0
21
1
1
Order By: Relevance
“…Several studies have previously evaluated photographs of the CVS [7, 8, 11]. The rate of conclusive photographs in the current study was lower than in the other studies.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Several studies have previously evaluated photographs of the CVS [7, 8, 11]. The rate of conclusive photographs in the current study was lower than in the other studies.…”
Section: Discussioncontrasting
confidence: 55%
“…It should be documented in the operation notes and preferably supported by intraoperative images. Two Dutch studies that assessed whether photographs or video images performed better at documenting the CVS yielded contradictory results [7, 8]. In both studies, the CVS (and thus, cystic duct identification) could be registered conclusively for only 34–70% of the patients.…”
mentioning
confidence: 99%
“…Therefore, the current legislation needs a practical translation for use in a clinical setting. It is advisable to [30] showed that agreement among health care professionals with regard to defining proper care can be poor, but Emous et al [31] showed that interobserver reliability is improved when video data are used instead of photos. Finally, video data do not necessarily contain information that is supplementary to other available data, in which case it has no added value.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,14 Ideally, a shortened video exhibiting such key steps (eg, the critical view of safety in cholecystectomy) would be kept in addition to the full, unaltered version, so that providers can readily view select footage in a reasonable period of time. It is our strong opinion that using video cameras, which are already present in our operating rooms, is a necessary endeavor that will lead to increased patient safety and improved operative outcomes.…”
Section: Forward Thinkingmentioning
confidence: 99%